(untitled) (Research, Society and Development, 2023)
The objective of this investigation is to understand the daily lives of nurses who work in the Family Health Strategy regarding home visits to therapeutic residences. Methodology: A descriptive study with a qualitative approach, from the perspective of Michel Maffesoli’s Comprehensive Sociology, which discusses the importance of considering the phenomenon itself, seeking a new vision and awareness of the world, and searching for identifying what goes beyond what is intended to be realized, spoken, and demonstrated. Five nurses were interviewed who work in a municipality in the Zona da Mata Mineira region in primary health care units whose care model is the Family Health Strategy and whose catchment area includes Therapeutic Residential Services. Results and discussions: three categories emerged from the analysis: institutionalizing the Therapeutic Residential Service; biomedicine in evidence as the motivation for home visits to the Therapeutic Residential Services; and the "little big things" that point to madness as a stigma and weaken the social inclusion of the residents of the Therapeutic Residential Services. These highlight the daily lives of nurses regarding mental health care, pointing out weaknesses in this process in line with the proposals of the Psychiatric Reform Act. Conclusions: It was understood that nurses’ relationship with mental health care is weakened and stigmatized, and that they do not recognize therapeutic residences as homes but as asylum institutions, thus compromising the integrality of care and the social inclusion of people with mental disorders.